Palm Springs Spa Hotel exterior by Julius Shulman - Julius Shulman::::::photographer:::
Photograph of exterior view of the Palm Springs Spa Hotel featuring the hotel's colonnade entrance and seating. Stamped "Photography by Julius Shulman" on the back.